Summarize the results of study on atmospheric corrosion in vietnam - Le Thi Hong Lien (Vietnam Journal of Science and Technology, 2017)
This paper summarizes the main results of field study on atmospheric corrosion in Vietnam since 1995 by now including corrosion of carbon steel, zinc coatings and copper. The climate characteristics and deposition rate of chloride and sulfur dioxide were determined during time of exposure. The results show that corrosion of carbon steel is mostly accelerated by the time of wetness and decreases with temperature increasing, meanwhile the corrosion of zinc coating and copper seems not to be dominated by humidity but by air salinity and the other factors such as rain regime, SO2 content, and so on. In the coastal areas, the Cl- content of the air has accelerated effect on corrosion of all tested materials. The long term testing data show that corrosion of tested materials develops mainly according to power law, however in some cases it follows linear or logarithm law depends on the protectiveness of corrosion product layer formed on the surface. The atmospheric corrosivity of Vietnam was classified according to ISO 9223 based on TOW, SO2 and Cl- content. The corrosion mapping was done preliminary for non-coastal areas. The studies in the current time and near future are also informed in the paper.